Characterization of the sound insulation properties of a two-layers lightweight concrete innovative façade. (February 2019) - Calleri, Cristina; Astolfi, Arianna; Shtrepi, Louena; Prato, Andrea; Schiavi, Alessandro; Zampini, Davide; Volpatti, Giovanni
Abstract: This study aims to characterize the sound insulation properties of a two-layers innovative façade made by a Structural Concrete Wall with Thermal Insulation Properties (SCWTIP). The sound reduction index of the wall has been evaluated through analytical calculation, software simulation and laboratory measurement on a 10 m 2 real sample, according to EN ISO 10140-2. Results showed that analytical calculation matches laboratory measurements in terms of sound reduction index, while 1 dB increase has been found with software simulation. Software simulations have also been carried out in order to compare the sound insulation index of the tested wall with walls in which the mechanical properties or the thicknesses of the concrete layers have been varied, in consideration of the commercially available options. Calculation of the standardized sound level difference of façade according to EN ISO 12354-3 for a typical dwelling room showed that a lightweight concrete façade made with this technology satisfies the requirements of the higher class set by the COST Action TU0901 for sound insulation of dwellings. The requirement set by French laws, which is not included in the Action framework, has been also accomplished.